Increasing the hiding capacity of low-bit encoding audio steganography using a novel embedding technique - Olanweraju, Rashidah Funke; Khalifa, Othman Omran; Abdul Rahman @ Sulaiman, Husna (IDOSI Publication, 2013)
The rapid growth of multimedia transmission leads to lose the owner identity of their products. Therefore, the demand to secure such input is crucial. In this paper, an overview of steganography and its technique applied is introduced. A data hiding within audio signals is studied. LSB technique is used and simulated result is presented. The result is characterized by robustness and high bit rate. It was shown that length of the embedded message (secret message) does not affect the stego signal audibility as long as it does not exceed the length of the original signal.